International Portfolio Diversification: United States and South Asian Equity Markets - Mushtaq, Rizwan; Zulfiqar Ali Shah, Syed (Panoeconomicus, 2014)
This paper explores the dynamic liaison between US and three developing South Asian equity markets in short and long term. To gauge the long-term relationship, we applied Johansen co-integration procedure as all the representative indices are found to be non-stationary at level. The findings illustrate that the US equity market index exhibits a reasonably different movement over time in contrast to the three developing equity markets under consideration. However, the Granger-causality test divulge that the direction of causality scamper from US equity market to the three South Asian markets. It further indicates that within the three developing equity markets the direction of causality emanates from Bombay stock market to Karachi and Colombo. Overall, the results of the study suggest that the American investors can get higher returns through international diversification into developing equity markets, while the US stock market would also be a gainful upshot for South Asian investors. Key words: International portfolio diversification, South Asian stock markets, Co-integration and causality. JEL: C32, G11, G15.